Conhecimento sobre poluição e acidentes de trabalho entre escolares residentes em área impactada por aterro sanitário - Gomes, Rosangela Maiara Vindoura (2015)
The transformations that man has caused in the environment over the years, has generated consequences in changing the balance in nature, these reflected in their own health. The relationship between health and environment deserves attention because worldwide diseases that were attributed to environmental causes reached 25% in 2006. The pollution contributes significantly to diseases attributed to environmental causes. Allied to these diseases from the environment are injuries and work-related diseases, which are not restricted to the adult population. In this context, the promotion of educational activities with school becomes a priority to ensure participation and the promotion of knowledge about the reality that influence the health-disease process. The purpose of this research is to analyze the knowledge about pollution and accidents in children living in the impacted area for landfill before and after an educational program. This is an analytical cross-sectional study, with the school population enrolled in the fifth to the ninth grade of elementary school. The location of the study was on the District Coxipó do Ouro, near the landfill of Cuiabá. Was applied selfadministered questionnaire before and after an educational program on health. We conducted univariate analysis of absolute and relative frequencies, and the bivariate association having as measure the prevalence ratio (PR) using the Chi-square test and Fisher's exact test with level of significance 0.05 and IC = 95%. There was a significant increase in knowledge about pollution after the implementation of educational activities and the existence of prior knowledge on topics related to environmental pollution. With regard to accidents at work there was a statistically significant increase in knowledge about occupational accident after the development of the program (p <0.05), showing the school as a privileged space in the development of activities for the prevention of accidents and diseases work. Faced with the reality found on the site of the research note is that there are school need to work with themes that are part of the life of the school so that they develop knowledge that will help them to think of integrated health and environment shape, and how this can interfere with human health.